Young people in residential aged care: Is Australia on track to meet its targets?. Issue 2 (7th September 2021) - Brown, Mark; Condi, Amelia; Davis, Elise; Goodwin, Isabella; Winkler, Di; Douglas, Jacinta
Abstract: Over 4500 people under 65 years of age live in residential aged care (RAC) in Australia, and they experience poorer quality of life than people with similar disabilities in other settings. Governments have long aimed to reduce admissions of young people to RAC, but in 2019, for the first time, the Australian Government adopted target dates for resolving the issue. The targets include reducing admissions of young people to near zero by 2022 and ensuring almost no one remains in RAC beyond 2025. The national strategy focuses mostly on housing and support needs being met via the National Disability Insurance Scheme. The present study drew on quarterly data from the National Aged Care Data Clearinghouse to examine progress toward these targets. Significant progress was evident in terms of young people entering RAC: admissions reduced each quarter between September 2018 and July 2020, halving over two years. No progress was evident in terms of young people leaving RAC for better arrangements; the trend neither increased nor decreased. Prospects for achieving the targets are discussed.